Pregunta
upstudy study bank question image url

Q4. (i) Find the exact solution of the equation \[ 8^{2 x+1}=6 \] giving your answer in the form \( a+b \log _{2} 3 \), where \( a \) and \( b \) are constants to be found. (ii) Using the laws of logarithms, solve \[ \log _{5}(7-2 y)=2 \log _{5}(y+1)-1 \]

Ask by Reyes Martinez. in Qatar
Feb 17,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

(i) \( x = -\frac{1}{3} + \frac{1}{6} \log_{2} 3 \) (ii) \( y = -6 + \sqrt{70} \)

Solución

We solve each part step by step. ───────────────────────────── Part (i) We need to solve   8^(2x + 1) = 6 Step 1. Express 8 as a power of 2. Since 8 = 2³, we can rewrite the left side:   (2³)^(2x + 1) = 2^(3(2x + 1)) = 2^(6x + 3). Thus the equation becomes   2^(6x + 3) = 6. Step 2. Take logarithms with base 2 of both sides:   6x + 3 = log₂6. Step 3. Solve for x:   6x = log₂6 – 3   x = (log₂6 – 3) / 6. Step 4. Write log₂6 in a form that involves log₂3. Note that 6 = 2 × 3, so   log₂6 = log₂2 + log₂3 = 1 + log₂3. Substitute back:   x = (1 + log₂3 – 3) / 6 = (log₂3 – 2) / 6. This can be rearranged to emphasize the required form a + b·log₂3:   x = –2/6 + (1/6)·log₂3 = –1/3 + (1/6)·log₂3. Thus, the constants are a = –1/3 and b = 1/6. ───────────────────────────── Part (ii) We need to solve   log₅(7 – 2y) = 2·log₅(y + 1) – 1. Step 1. Use the logarithm laws. Express the right-hand side as a single logarithm. Notice:   2·log₅(y + 1) = log₅((y + 1)²). Also, recall that subtracting 1 is equivalent to subtracting log₅5 because log₅5 = 1. Hence,   2·log₅(y + 1) – 1 = log₅((y + 1)²) – log₅5 = log₅[(y + 1)²/5]. So the equation becomes   log₅(7 – 2y) = log₅[(y + 1)²/5]. Step 2. Equate the arguments (the expressions inside the logarithms) provided they are positive:   7 – 2y = (y + 1)² / 5. Step 3. Multiply both sides by 5:   5(7 – 2y) = (y + 1)²   35 – 10y = y² + 2y + 1. Step 4. Rearranging to set the quadratic to zero:   0 = y² + 2y + 1 + 10y – 35   0 = y² + 12y – 34. This is the quadratic equation:   y² + 12y – 34 = 0. Step 5. Use the quadratic formula, y = [–b ± √(b² – 4ac)] / (2a), where a = 1, b = 12, and c = –34:   Discriminant: Δ = 12² – 4(1)(–34) = 144 + 136 = 280. Thus,   y = [–12 ± √280] / 2. Since √280 = 2√70, then   y = [–12 ± 2√70] / 2 = –6 ± √70. Step 6. Check the domain restrictions. For the logarithms we need:   a) y + 1 > 0 ⟹ y > –1,   b) 7 – 2y > 0 ⟹ y < 7/2 = 3.5. Evaluate both solutions:   • y = –6 – √70 is much less than –1 (and thus invalid).   • y = –6 + √70. Since √70 ≈ 8.37, we get y ≈ 2.37, which satisfies y > –1 and y < 3.5. Thus the unique solution is   y = –6 + √70. ───────────────────────────── Final Answers (i) x = –1/3 + (1/6)·log₂3   (with constants a = –1/3, b = 1/6) (ii) y = –6 + √70.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

To solve the equation \( 8^{2x+1}=6 \), we can rewrite it using base 2: since \( 8 = 2^3 \), we have \[ (2^3)^{2x + 1} = 6 \implies 2^{6x + 3} = 6. \] Taking logarithms of both sides, we get \[ 6x + 3 = \log_2 6 \implies 6x = \log_2 6 - 3 \implies x = \frac{\log_2 6 - 3}{6}. \] Now, \( \log_2 6 \) can be expressed as \( \log_2 (2 \cdot 3) = \log_2 2 + \log_2 3 = 1 + \log_2 3 \). Substituting this into our expression for \( x \): \[ x = \frac{(1 + \log_2 3) - 3}{6} = \frac{\log_2 3 - 2}{6} = -\frac{1}{3} + \frac{1}{6} \log_2 3. \] Thus, in the form \( a + b \log_2 3 \), we find \( a = -\frac{1}{3} \) and \( b = \frac{1}{6} \). --- For the logarithmic equation \( \log_{5}(7-2y)=2 \log_{5}(y+1)-1 \), we can first rewrite the right side. Using properties of logarithms, \( 2 \log_{5}(y+1) \) can be expressed as \( \log_{5}((y+1)^2) \). Thus, we have: \[ \log_{5}(7-2y) = \log_{5}((y+1)^2) - 1. \] Now, recall that subtracting 1 is equivalent to dividing by 5: \[ \log_{5}(7-2y) = \log_{5}\left(\frac{(y+1)^2}{5}\right). \] If we drop the logs (since the bases are the same), we find: \[ 7 - 2y = \frac{(y+1)^2}{5}. \] Multiplying both sides by 5 results in: \[ 5(7 - 2y) = (y + 1)^2. \] This simplifies to: \[ 35 - 10y = y^2 + 2y + 1, \] which can be rearranged to form a quadratic equation: \[ y^2 + 12y - 34 = 0. \] Using the quadratic formula \( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): \[ y = \frac{-12 \pm \sqrt{12^2 - 4 \cdot 1 \cdot (-34)}}{2 \cdot 1} = \frac{-12 \pm \sqrt{144 + 136}}{2} = \frac{-12 \pm \sqrt{280}}{2}. \] Simplifying, we find: \[ y = \frac{-12 \pm 2\sqrt{70}}{2} = -6 \pm \sqrt{70}. \] Thus, the solutions to the equation are: \[ y = -6 + \sqrt{70} \quad \text{or} \quad y = -6 - \sqrt{70}. \] Only \( -6 + \sqrt{70} \) is a valid solution since \( y \) must satisfy \( y+1 > 0 \).

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad